Design of optical sighting telescope training system based on simulated target. Issue 1 (April 2021) - Li, Menglei; Rong, Yingjiao; Wang, Shirui; Wang, Yuchen; Sun, Ping
Abstract: In order to solve the practical operation training problem of an optical sighting telescope in certain weapon system, the application research of simulated target technology is carried out. According to the tactical and technical characteristics of sight and battlefield target, based on the embedded simulation framework, a series of simulation target technologies, such as constructing the optical characteristic model of target, fitting the target trajectory, encapsulating the characteristic information of target in the typical scene, are used to explore the technical route of actual combat training relying on actual equipment and simulation target, and realize the training scene and its model. The application results show that the method is feasible.